Pengaruh QuizWhizzer terhadap Motivasi Belajar Siswa pada Pembelajaran IPA di SMPN 1 Palangka Raya - Tyarini, Elly Brata; Araina, Elga; Putri, Rahmadyah Kusuma; Rahmawati, Rahmawati; Hartanti, Rio Eka Desi Purwandari (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the effect of QuizWhizzer on student learning motivation in science lessons for eighth graders at SMPN 1 Palangka Raya. This study is quantitative in nature and uses an experimental research method. The research design used in this study is a one-group pre-test and post-test design with one class as the sample, consisting of 28 students. The media used in this study was QuizWhizzer, which is an educational game-based media. The instrument used in data collection was a questionnaire with a 4-point Likert scale, which was a modification of the 5-point Likert scale. The results showed that the average score of student learning motivation after being given treatment at the post-test was 62, which was very good. Data analysis results showed an increase in student learning motivation, accompanied by significant positive changes (sig. 0.000<0.05). Based on these findings, the researcher concluded that the use of QuizWhizzer media had a positive effect on student learning motivation.